중국의 지역발전전략과 패러다임 적용에 관한 고찰: 균형성장론과 불균형성장론 간의 비교론적 접근을 중심으로 - 김남이 (한국비교정부학보, 17(2), 2013)
Regional development refers to a series of economic and social activities to gain economic and social profits by carrying out exploitation and production of resources and reformation of the structure of industries in specific or targeted areas. For this reason, government mobilization of strategic instruments to attain these purposes may be defined as the regional development strategy. This paper inquires into some of the development theories and makes critical reflections on established theories on regional development and comparative investigations of the balanced growth theory and the unbalanced growth theory. The main points of the regional development strategy, which has been helping economic growth in China, can be derived from these inquiries, reflections and investigations. The balanced growth theory and the unbalanced growth theory serve as the theoretical approach used for a subject under discussion in this paper. How does the paradigm of regional development concretely apply to the regional development strategy in China? What is the core of this change of strategy in China? These questions are discussed in this paper. KCI Citation Count: 3